Pentaarylcyclopentadienyl Iron, Cobalt, and Nickel Halides - Chakraborty, Uttam; Modl, Moritz; Muehldorf, Bernd; Bodensteiner, Michael; Demeshko, Serhiy; Van Velzen, Niels J. C.; Scheer, Manfred; Harder, Sjoerd; Wolf, Robert (Inorganic Chemistry, 2016)
The preparation of new stable half-sandwich transition metal complexes, having a bulky cyclopentadienyl ligand C-5(C6H4-4-Et)(5) (Cp-Ar1) or C-5(C6H4-4-nBu)(5) (Cp-Ar2), is reported. The tetrahydrofuran (THF) adduct [(CpFe)-Fe-Ar1(mu-Br)(THF)](2) (1a) was synthesized by reacting K[Cp-Ar1] with [FeBr2(THF)(2)] in THF, and its molecular structure was determined by X-ray crystallography. Complex 1a easily loses its coordinated THF molecules under vacuum to form the solvent-free complex [(CpFe)-Fe-Ar1(mu-Br)](2) (1b). The analogous complexes [(CpCo)-Co-Ar1(mu-Br)](2) (2), [(CpNi)-Ni-Ar1(mu-Br)](2) (3), and [(CpNi)-Ni-Ar2(mu-Br)](2) (4) were synthesized from CoBr2 and [NiBr2(1,2-dimethoxyethane)]. The mononuclear, low-spin cobalt(III) and nickel(III) complexes [(CpMI2)-M-Ar2] (5, M = Co; 6, M = Ni) were prepared by reacting the radical Cp-Ar2 with NiI2 and CoI2. The complexes were characterized by NMR and UV-vis spectroscopies and by elemental analyses. Single-crystal X-ray structure analyses revealed that the dimeric complexes 1a, 1b, and 3 have a planar M2Br2 core, whereas 2 and 4 feature a puckered M2Br2 ring.